REVIEW OF THE “SILO QUAKING” PROBLEMS IN BINS OF VARIOUS GEOMETRICAL SHAPES AND FLOW PATTERNS - ALAN W. ROBERTS (TASK Quarterly, 2003)
The paper reviews the characteristics of pulsating or cyclic flow of bulk solids during gravity discharge in bins and silos. The dynamic load phenomenon is often referred to as “silo quaking” and is known to occur in silos of various geometrical shapes, operating under different flow patterns. Examples include mass-flow, funnel-flow, expanded-flow, multi-outlet bins and bins operating under intermediate-flow. While silo quaking is often associated with tall bins, depending on the flow pattern, the problem can also be experienced in bins of squat proportions. The period of pulsations during flow is influenced by various factors, such as, particle size and size distribution, silo wall material and wall roughness, internal friction, moisture content and discharge flow rate. Of particular relevance is the influence of slip-stick effects during shear flow, and velocity at critical sections in the silo during discharge. The paper presents an overview of silo quaking with case studies to illustrate the range of problems that can occur.